Assessing Effects of Transit Signal Priority on Traffic Safety: Empirical Bayes Before–After Study using King County, Washington, Data. Issue 8 (December 2018) - Song, Yu; Noyce, David
Transit signal priority (TSP) has become popular among cities in the United States as a transit preferential treatment that improves transit operational performance through adjusting signal timing when transit vehicles are approaching signalized intersections. The majority of attention has been given to the operational effects of TSP. A small number of prior studies have discussed such a system's effects on traffic safety, with few studies investigating North American implementations. Prior assessment results were mixed, leaving the understanding of TSP's safety effects unclear. The purpose of this study was to add to the existing research on this topic, and to get a better understanding of TSP's safety effects. An empirical Bayes (EB) before–after analysis was carried out using TSP implementation data from King County, Washington. Eleven transit corridors having had TSP activated in 2010–2014 were assessed, and 75 street sections without TSP treatment were selected to form a reference group. The EB analysis results showed a 13% reduction in total crashes with the implementation of TSP, a 16% reduction in property-damage-only crashes, and a 5% reduction in fatal and injury crashes. These results are consistent with most existing TSP safety studies. The study implies that TSP brings road safety benefits to transit corridors in a U.S. metropolitan setting, and suggests that transportation and transit agencies add safety assessment into future TSP practices.